Experimental study and clinical significance of the impact of gastrointestinal motility disorders on hepatic blood perfusion - Tonghui, Jin; Tiejun, Liu; Chaoyue, Liu; Han, Wang (Frontiers in Medicine, 2025)
IntroductionThe gastrointestinal tract and liver maintain intricate hemodynamic relationships through the portal venous system. While gastrointestinal motility disorders are known to affect digestive function, their impact on hepatic blood perfusion remains poorly understood—particularly in the context of hepato-gastrointestinal interactions—limiting comprehensive patient management approaches. This study aimed to investigate the mechanism and clinical significance of the impact of gastrointestinal motility disorders on hepatic blood perfusion, providing a theoretical basis for the diagnosis and treatment of related diseases.MethodsSixty patients with gastrointestinal motility disorders, admitted from January 2023 to December 2024, were selected as the study group, with 60 healthy individuals during the same period forming the control group. Hepatic blood perfusion status was evaluated through abdominal ultrasound Doppler and CT perfusion imaging, while gastrointestinal motility function was assessed using electrogastrography and gastrointestinal motility monitoring systems.ResultsPortal vein flow velocity, hepatic arterial blood flow, and hepatic perfusion index in patients with gastrointestinal motility disorders were significantly lower than those of individuals in the control group (p < 0.05). The degree of gastrointestinal motility disorder showed a significant negative correlation with hepatic perfusion parameters (r = −0.681, p < 0.01), with clinically significant thresholds identified for intervention planning.DiscussionGastrointestinal motility disorders can significantly affect hepatic blood perfusion status. Clinically, attention should be paid to changes in liver function in patients with these disorders, focusing on early intervention to improve prognosis. These findings have important implications for clinical monitoring protocols and treatment strategies.